The extended spatial distribution of globular clusters in the core of the Fornax cluster - D'Abrusco, Raffaele; Grebel, Eva K.; Lisker, Thorsten; Wittmann, Carolin (Arxiv, 2016)
We report the discovery of a complex extended density enhancement in the Globular Clusters (GCs) in the central $\sim 0.5(^{°})^2$ ($\sim 0.06$ Mpc$^2$) of the Fornax cluster, corresponding to $\sim 50%$ of the area within 1 core radius. This overdensity connects the GC system of NGC1399 to most of those of neighboring galaxies within $\sim 0.6^{°}$ ($\sim 210$ kpc) along the W-E direction. The asymmetric density structure suggests that the galaxies in the core of the Fornax cluster experienced a lively history of interactions that have left a clear imprint on the spatial distribution of GCs. The extended central dominant structure is more prominent in the distribution of blue GCs, while red GCs show density enhancements that are more centrally concentrated on the host galaxies. We propose that the relatively small-scale density structures in the red GCs are caused by galaxy-galaxy interactions, while the extensive spatial distribution of blue GCs is due to stripping of GCs from the halos of core massive galaxies by the Fornax gravitational potential. Our investigations is based on density maps of candidate GCs extracted from the multi-band VLT Survey Telescope (VST) survey of Fornax (FDS), identified in a three-dimensional color space and further selected based on their
Gesehen am 08.11.2017